Multiview Image Coding Based on Geometric Prediction - San, Xiang; Cai, Hua; Lou, Jian-Guang; Li, Jiang (IEEE Transactions on Circuits and Systems for Video Technology, 2007)
Many existing multi-view image/video coding techniques remove inter-viewpoint redundancy by applying disparity compensation in a conventional video coding framework, e.g. H.264/MPEG-4 AVC. However, conventional methodology works ineffectively as it ignores the special characteristics of inter-viewpoint disparity. In this paper, we propose a geometric prediction methodology for accurate disparity vector (DV) prediction, such that we can largely reduce the disparity compensation cost. Based on the new DV predictor, we design a basic framework that can be implemented in most existing multi-view image/video coding schemes. We also use state-of-the-art H.264/MPEG-4 AVC as an example to illustrate how the proposed framework can be integrated with conventional video coding algorithms. Our experiments show proposed scheme can effectively tracks disparity and greatly improves coding performance. Compared with H.264/MPEG-4 AVC codec, our scheme outperforms maximally 1.5 dB when encoding some typical multi-view image sequences. We also carry out an experiment to evaluate the robustness of our algorithm. The results indicate our method is robust and can be used in practical applications.